Pengenaan Denda Pajak atas Penerbitan Faktur Pajak Digunggung (Studi Kasus Putusan Pengadilan Pajak Nomor PUT-009994.99/2024/PP/M.VIB Tahun 2025) - maralus samosir; Eduward Tony Sitorus (CV Rewang Rencang, 2024)
This research examines the taxation between CV Utama Jaya Selular as a Taxpayer and the Directorate General of Taxes regarding the imposition of administrative fines based on Article 14 paragraph (4) of the Law on General Provisions and Tax Procedures on Tax Invoices (STP) for Value Added Tax (VAT) for the June 2020 Tax Period. The dispute focuses on the discrepancy in tax collection alleged by the Plaintiff for the delivery of Taxable Goods (BKP) to consumers according to the end. The research method used is the normative legal research method, namely research that emphasizes the study of laws and regulations, jurisprudence, and legal doctrine with a qualitative approach. The results show that the Plaintiff claims to have delivered BKP and issued a tax invoice in accordance with the regulations, without harming the state because the final buyer cannot credit VAT. On the other hand, the Defendant considers that there is a delivery to a buyer who is not the final consumer so that a standard invoice must be issued and violations are subject to administrative sanctions. The Tax Court stated that the invoice in question was valid because the buyer data was incomplete and the VAT reporting did not harm the state, so the STP and sanctions were canceled. The research emphasizes the importance of understanding the characteristics of end consumers and the provisions of tax invoices in the implementation of VAT and their impact on administrative sanctions, contributing to the tax law literature in Indonesia.